Women’s and Men’s Political Participation Training Curriculum - Kosec, Katrina; Kyle, Jordan (CGIAR System Organization, 2024)
Women’s and Men’s Political Participation Trainings are curricula developed jointly by ActionAid Nigeria and the CGIAR to strengthen women’s sense of collective efficacy and leadership skills, and to increase men’s support for women’s voice and agency. The curricula thus help raise women’s voice and agency through interactions with women as well as their husbands.